2023
DOI: 10.3390/vaccines11010100
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Nano-Assemblies Circumvent Intrinsic Toxicity and Ensure Superior Protection in Experimental Visceral Leishmaniasis with Feeble Toxic Manifestation

Abstract: In spite of its high effectiveness in the treatment of both leishmaniasis as well as a range of fungal infections, the free form of the polyene antibiotic amphotericin B (AmB) does not entertain the status of the most preferred drug of choice in clinical settings. The high intrinsic toxicity of the principal drug could be considered the main impedance in the frequent medicinal use of this otherwise very effective antimicrobial agent. Taking into consideration this fact, the pharma industry has introduced many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Various strategies have been developed to avoid the haemolytic and cytotoxic activity of the compounds, such as their molecular modification [39] or the use of drug delivery systems, some already in clinical use and others being evaluated in clinical trials [40]. Amphotericin B is a good example of an antifungal drug widely used in the treatment of serious systemic infections, with a broad spectrum of action and a very low level of resistance, but which is very toxic to humans [41][42][43][44]. The toxicity associated with amphotericin B has implications for its clinical use, which is limited to inpatients due to the need, among other factors, for slow continuous intravenous infusion and the permanent need to monitor renal toxicity and body temperature [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various strategies have been developed to avoid the haemolytic and cytotoxic activity of the compounds, such as their molecular modification [39] or the use of drug delivery systems, some already in clinical use and others being evaluated in clinical trials [40]. Amphotericin B is a good example of an antifungal drug widely used in the treatment of serious systemic infections, with a broad spectrum of action and a very low level of resistance, but which is very toxic to humans [41][42][43][44]. The toxicity associated with amphotericin B has implications for its clinical use, which is limited to inpatients due to the need, among other factors, for slow continuous intravenous infusion and the permanent need to monitor renal toxicity and body temperature [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B is a good example of an antifungal drug widely used in the treatment of serious systemic infections, with a broad spectrum of action and a very low level of resistance, but which is very toxic to humans [41][42][43][44]. The toxicity associated with amphotericin B has implications for its clinical use, which is limited to inpatients due to the need, among other factors, for slow continuous intravenous infusion and the permanent need to monitor renal toxicity and body temperature [41][42][43][44]. For this reason, new therapeutic systems have been developed for administering this drug, and it continues to be used in therapy [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] This scientific study revealed that the new formulation of Am‐B has minimal toxicity on living cells (erythrocytes, RBCs). [ 18 ] Furthermore, Singh et al., 2022 showed the promising antileishmanial activity of carboxymethyl chitosan (CMC)‐Am‐B‐LV (with no toxicity) against L. donovani infected macrophages. [ 19 ] These data indicated that newly designed carrier systems for drug delivery can increase efficacy and also reduce cytotoxicity of Am‐B (Table 1).…”
Section: Nanomedicine and Nano‐based Drug Delivery Systemsmentioning
confidence: 99%
“…This formulation of Am‐B is highly effective against both promastigotes and amastigotes of Leishmania donovani . [ 18 ] This scientific study revealed that the new formulation of Am‐B has minimal toxicity on living cells (erythrocytes, RBCs). [ 18 ] Furthermore, Singh et al., 2022 showed the promising antileishmanial activity of carboxymethyl chitosan (CMC)‐Am‐B‐LV (with no toxicity) against L. donovani infected macrophages.…”
Section: Nanomedicine and Nano‐based Drug Delivery Systemsmentioning
confidence: 99%